Relationship between manganese minerals and type 2 diabetes mellitus - Izna Nurdianty Muhdar (Arsip Keilmuan Gizi (AKG), 2024)
Indonesia is the fourth country with the largest prevalence of DM in the world which is caused by an unhealthy lifestyle. Risk factors for DM that cannot be modified include race, ethnicity, age, gender, genetics from a family with DM, history of giving birth >4 kg and LBW <2.5 kg. Meanwhile risk factors that can be modified include overweight, abdominal/central obesity, lack of physical activity, high blood pressure (hypertension), dyslipidemia, high calorie and unbalanced diet, prediabetes with impaired blood glucose tolerance levels (IGT 140 -199 mg/dl) or impaired fasting blood glucose levels (GDPT <140 mg/dl) as well as smoking habits. Several studies have revealed that dietary manganese is related to type 2 DM. However, the relationship between manganese diet and type 2 DM in women cannot yet be explained through a definite pathophysiological pathway after all confounding variables have been adjusted for, so it still needs to be studied further, especially regarding manganese analysis methods in assessing manganese status. which is usually based on the concentration of manganese in plasma/serum and all blood components.